Rutas y protocolos para la inclusión educativa de estudiantes con autismo grado 1 en la Universidad Nacional de Chimborazo. - Toledo Pavón, Nancy Mercedes (2025)
The present research focuses on the educational inclusion of students with Level 1Autism at the National University of Chimborazo (UNACH), a challenge that requires the creation of specific routes and protocols to ensure their access, retention, and academic success. Educational inclusion is a fundamental right that seeks to ensure that all students, regardless of their individual characteristics, can fully participate in the educational environment. The justification for this proposal lies in the need to adequately support students with autism, who face significant barriers to their integration. Through a qualitative approach, a diagnosis was conducted that revealed a lack of knowledge and resources regarding autism within the university community, highlighting the urgency of developing effective strategies. The general objective of the research is to implement routes and protocols that facilitate the inclusion of these students, while the specific objectives include training staff, adapting curricula, ensuring physical space accessibility, and promoting emotional and social well-being. Routes and protocols are presented in four key aspects: academic, administrative, physical space adaptation, and well-being. In the academic aspect, staff training and the creation of individualized adaptation plans are proposed. In the administrative domain, the aim is to establish inclusive policies and a flexible admission process. The adaptation of physical spaces focuses on ensuring accessibility and creating support zones. Finally, well-being is promoted through emotional support programmes and activities that foster social inclusion. The research concludes that the creation of these routes and protocols will not only Benefit students with autism but will also enrich the university community, promoting an environment of diversity and empathy. A firm institutional commitment is recommended to carry out these initiatives and ensure an inclusive and accessible educational environment for all.